2017
DOI: 10.1515/humo-2017-0044
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of network processes between successful and unsuccessful offensive sequences in elite soccer

Abstract: Purpose. The study aimed to compare social network analysis (SNA) general measures and centrality levels of successful and unsuccessful offensive sequences performed by elite national teams in 64 matches of the FIFA World Cup 2014 tournament and to compare the level of centrality between playing positions. Methods. Adjacency matrices of passing sequences within an offensive unit were built and treated in a dedicated SNA software.Results. The main results indicated significantly lower values of total links and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…On the other hand, the micro interaction analyses according to playing positions within categories showed a higher prominence of midfielders in the U-14 category. These results are in line with the results of previous studies on the formal game 24 and SSG 1 , in which midfielders presented a more active role for constructing offensive actions, taking the ball from the defensive to the offensive field 24 . Midfielders are also important for organizing the defensive actions during the defensive transition because they are usually closer to the game center and, therefore, can properly direct opponents to lower risk areas and create numerical superiority in the game center.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the micro interaction analyses according to playing positions within categories showed a higher prominence of midfielders in the U-14 category. These results are in line with the results of previous studies on the formal game 24 and SSG 1 , in which midfielders presented a more active role for constructing offensive actions, taking the ball from the defensive to the offensive field 24 . Midfielders are also important for organizing the defensive actions during the defensive transition because they are usually closer to the game center and, therefore, can properly direct opponents to lower risk areas and create numerical superiority in the game center.…”
Section: Discussionsupporting
confidence: 92%
“…Since no interactions between main effects were observed, two different analysis were conducted for this aim: a comparison between different playing positions within each match status and a comparison between different match statuses within each playing position. In this topic, many studies have discussed the characteristics of each playing position during a football match (López-Peña and Touchette, 2012; Peixoto et al, 2017). For example, CM presented the highest frequencies of successful passes and receptions (Brito et al, 2017), and the highest prominence in official matches (López-Peña and Touchette, 2012; Peixoto et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this topic, many studies have discussed the characteristics of each playing position during a football match (López-Peña and Touchette, 2012; Peixoto et al, 2017). For example, CM presented the highest frequencies of successful passes and receptions (Brito et al, 2017), and the highest prominence in official matches (López-Peña and Touchette, 2012; Peixoto et al, 2017). Considering the need to regain the ball possession quickly, losing teams are expected to adopt a more aggressive defensive style, increasing the time constraint to the team in offense, which is in line with the study of Barreira et al (2015), who demonstrated that attacking teams increased their difficult to create a favorable numerical contexts in the game center over the years in modern soccer.…”
Section: Discussionmentioning
confidence: 99%
“…Results suggest a negative relationship between the success of offensive plays and network density, which is the only significant predictor variable in the model. This result was supported by Peixoto, Praça, Bredt, and Clemente (2017) who applied social network analysis to study differences across centrality measures in successful and unsuccessful offensive plays.…”
Section: Introductionmentioning
confidence: 75%
“…By only considering offensive sequences that ended with shots in their network analysis, Peixoto et al (2017) had a similar approach to Network 3. In-degree and out-degree centrality measures, which are linked to passes received and passes made, respectively, were calculated and revealed that strikers and midfielders scored highest on the respective measures.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%